2014
DOI: 10.1016/s1995-7645(14)60089-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenol content, antioxidant and tyrosinase inhibitory activity of mangrove plants in Micronesia

Abstract: Taken together, the results of this study proved that mangroves can be excellent sources of antioxidant compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 24 publications
2
23
2
6
Order By: Relevance
“…It was noted that the values of R. apiculata and S. alba superseded those of leaves of Hibiscus tiliaceus L. (42%) and Psidium guava L. (41%) (Wong et al, 2010), roots of Eurycoma longifolia Jack (45%) (Wan Hassan et al, 2015a), and pericarps of Garcinia mangostana L. (Wan Hassan et al, 2015b), which have strong anti-tyrosinase activity. Contrary to findings of this study, Suh et al (2014) reported that leaves, stems and roots of R. stylosa inhibited tyrosinase with the strongest activity in the stems (90%). Data on the anti-QS activity of the four mangrove species based on optical density of inhibition of C. violaceum growth and violacein production are shown in Table 4.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…It was noted that the values of R. apiculata and S. alba superseded those of leaves of Hibiscus tiliaceus L. (42%) and Psidium guava L. (41%) (Wong et al, 2010), roots of Eurycoma longifolia Jack (45%) (Wan Hassan et al, 2015a), and pericarps of Garcinia mangostana L. (Wan Hassan et al, 2015b), which have strong anti-tyrosinase activity. Contrary to findings of this study, Suh et al (2014) reported that leaves, stems and roots of R. stylosa inhibited tyrosinase with the strongest activity in the stems (90%). Data on the anti-QS activity of the four mangrove species based on optical density of inhibition of C. violaceum growth and violacein production are shown in Table 4.…”
Section: Resultscontrasting
confidence: 99%
“…At the species level, TPC and AEAC values of MD and OD leaves were comparable for R. apiculata and R. stylosa, higher in MD leaves for A. rumphiana and higher in OD leaves for S. alba. The highest values of TPC (3940 mg GAE/100 g) observed in MD leaves of A. rumphiana and AEAC (6920 mg AA/100 g) observed in OD leaves of S. alba were both 1.7 times lower than those of green tea with TPC of 6550 mg GAE/100 g and AEAC of 11740 mg AA/100 g. Finding from this study therefore contradicts the observation by Suh et al (2014) that mangrove teas have stronger antioxidant properties than green tea, despite differences in the methods of tea preparation and in the brands of green tea used.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…This method and is very simple and widely used. 26 As shown in Figure 1, the TPC varied from 21.85 ± 3.12 to 180.00 ± 12.5 mg GAE/g. Polystichum woronowii (180.00 ± 12.5 mg GAE/g) exhibited the highest amount of phenolic compounds, followed by Dryopteris affinis (112.54 ± 8.09 mg GAE/g) and Pteris cretica (71.86 ± 5.34 mg GAE/g).…”
Section: Total Phenol Contentmentioning
confidence: 87%
“…Many roots subjected to experimental damage to the treatments became discoloured and black on the damaged areas. This may have been caused by the large amount of tannins present in the roots (Suh et al, 2014). Tannins undergo oxidation and oxidative darkening produces red, brown and black pigments in the presence of moisture (Nemeth et al, 2013).…”
Section: Discussionmentioning
confidence: 99%